Associations Between Trajectory of Different Blood Pressure Components in Pregnancy and Risk of Adverse Birth Outcomes – A Real World Study - Ma S; Wu L; Yu Q; Chen D; Geng C; Peng H; Yu L; Zhang M (Dove Medical Press, 2021)
Shengqi Ma,1,* Lei Wu,2,* Qing Yu,3,* Donghui Chen,2 Chunsong Geng,3 Hao Peng,1 Lugang Yu,2 Mingzhi Zhang1 1Department of Epidemiology, School of Public Health, Medical College of Soochow University, Suzhou, Jiangsu, People's Republic of China; 2Department of Maternal and Child Health, Suzhou Industrial Park Centers for Disease Control and Prevention, Suzhou, Jiangsu, People's Republic of China; 3Department of Gynecology and Obstetrics, Suzhou Kowloon Hospital, Suzhou, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Lugang YuDepartment of Maternal and Child Health, Suzhou Industrial Park Centers for Disease Control and Prevention, 200 Suhong West Road, Industrial Park, Suzhou, 215123, People's Republic of ChinaTel +86 512 6761 4200Fax +86 512 6761 4233Email YLG@sipcdc.comMingzhi ZhangDepartment of Biostatistics, School of Public Health, Medical College of Soochow University, 199 Renai Road, Industrial Park, Suzhou, 215123, People's Republic of ChinaTel +86 512 6588 0079Fax +86 512 6588 0052Email zhangmingzhi@suda.edu.cnBackground: High blood pressure during pregnancy has been suggested to be associated with adverse birth outcomes (ABO), but it is unclear how different blood pressure changes and the extent of the effect. Therefore, we aimed to investigate the association between blood pressure trajectories (systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), pulse pressure (PP)) of pregnant women and ABO in a real-world study.Material and Methods: Leveraging 28,679 pregnant women and their fetuses from a register-based cohort from January 1, 2010, to December 31, 2019. Blood pressure trajectories were estimated by package "traj" in R software using real-world blood pressure data of routine antenatal care examinations. Logistic regression models were applied to examine the association between trajectories of different blood pressure components (SBP, DBP, MAP, and PP) during pregnancy and the risk of ABO.Results: Trajectories of all blood pressure components were identically labeled as low-stable, moderate-increasing, moderate-decreasing and high-stable. After adjusting for confounding factors, compared with pregnant women with the low-stable pattern, pregnant women with a high-stable or moderate-increasing pattern had a significantly increased risk of developing adverse birth outcomes. Pregnant women with a moderate-decreasing pattern had no significant increased risk of ABO but had a lower risk of adverse birth outcomes than those with a moderate-increasing pattern. The trajectories crossed at 17- 20 weeks of gestation for all blood pressure components.Conclusion: Our study results indicated that reduction and maintenance of blood pressure to a low level of less than 110 mmHg for SBP and 65 mmHg for DBP after 20 weeks of gestation would benefit prevention of adverse birth outcomes, regardless of the level of blood pressure at early pregnancy.Keywords: blood pressure, trajectory, pregnancy, adverse birth outcomes, real-world study